2020
DOI: 10.3390/md18070358
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Depth on the Morphology, Bacterial Clearance, and Respiration of the Mediterranean Sponge Chondrosia reniformis (Nardo, 1847)

Abstract: To support the successful application of sponges for water purification and collagen production, we evaluated the effect of depth on sponge morphology, growth, physiology, and functioning. Specimens of Eastern Mediterranean populations of the sponge Chondrosia reniformis (Nardo, 1847) (Demospongiae, Chondrosiida, Chondrosiidae) were reciprocally transplanted between 5 and 20 m depth within the Kaş-Kekova Marine Reserve Area. Control sponges at 5 m had fewer but larger oscula than their conspecifics at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 62 publications
4
22
0
Order By: Relevance
“…Although the comparison of the CR between different sponge species is challenging due to the intraspecies variability, the effect of sponge size, the morpho-physiological features, and the different units in which CR are expressed [4,25,73], our results are comparable with those reported for other Mediterranean species ( Supplementary Table S1). A careful analysis of the results requires further considerations related to the characteristics of the tested sponge.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Although the comparison of the CR between different sponge species is challenging due to the intraspecies variability, the effect of sponge size, the morpho-physiological features, and the different units in which CR are expressed [4,25,73], our results are comparable with those reported for other Mediterranean species ( Supplementary Table S1). A careful analysis of the results requires further considerations related to the characteristics of the tested sponge.…”
Section: Discussionsupporting
confidence: 83%
“…The importance of free bacteria in the diet of sponges [16] and the ability to concentrate and digest large numbers of microorganisms suggested that sponges could be effective in reducing bacterial abundance, including microbial pollution, caused by sewage in coastal areas [17], such as near mariculture facilities where bacteria, including potentially pathogenic species, are often abundant [18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As concerns sponges, findings obtained from about 20 years of field and laboratory research on more than 30 sponge species by Italian and international researcher teams suggest that in situ sponge-culture may be suitable for the eco-sustainable supply chain of sponge biomass for some target species [44,[53][54][55][56][57]. The sponge biomass obtained in polyculture systems has considerable potential from a commercial point of view, having good appeal for cosmetic or hobbyist production of natural biocides, or for the pharmaceutical industry thanks to their bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%